EPPR Strategic Plan - Emergency Prevention, Preparedness, and Response (EPPR) (Emergency Prevention, Preparedness and Response (EPPR), 2016)
"Emergency Prevention, Preparedness, and Response (EPPR) Working Group, one of the six standing working groups, is mandated to contribute to the prevention, preparedness and response to environmental and other emergencies, accidents, and Search and Rescue (SAR). While not an operational response organization, members of the Working Group conduct projects to address gaps, prepare strategies, share information, collect data, and collaborate with relevant partners on capabilities and research needs that exist in the Arctic. Projects and activities include development of guidance and risk assessment methodologies, coordination of response exercises and training, and exchange of information on best practices with regards to the prevention, preparedness and response to accidents and threats from unintentional releases of pollutants and radionuclides, and to consequences of natural disasters. EPPR is assigned the responsibility for maintaining the Operational Guidelines that implement the Agreement on Cooperation on Marine Oil Pollution Preparedness and Response in the Arctic (MOSPA) to which all Arctic Council countries are signatories. EPPR also supports the Agreement on Cooperation on Aeronautical and Maritime Search and Rescue (SAR) in the Arctic by addressing relevant lessons learned from SAR exercises and real incidents."